The Evolution of Values. Whitehead’s Theoretical Foundation of Culture (2023)
ABSTRACT: Hegel and Whitehead are the last two great metaphysicians of modernity. However, despite comparable basic assumptions such as the process character of reality, the organism as a paradigm and subjectivity as a fundamental principle, they develop an opposing picture of the universe. While according to Whitehead nature is determined as creative activity and from his point of view the teleology of the universe is directed towards the production of beauty, Hegel sees the objective sense of the history of the world in the realization of reason by humans. Therefore, natural philosophy has only a subordinate position in Hegel’s work, whereas in Whitehead’s work the concept of nature is of central importance.